Development and analysis of an integrated system with direct splitting of hydrogen sulfide for hydrogen production - Al-Zareer, Maan; Dincer, Ibrahim; Rosen, Marc A. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This paper analyzes the thermodynamic performance of the combination of a water gas shift membrane reactor and an integrated coal gasification unit with a combined cycle, a carbon capture unit, and a unit for direct splitting of hydrogen sulfide into hydrogen and sulfur. The latter operates as an alternative process for disposing of hydrogen sulfide, while producing hydrogen. The purpose of the thermodynamic analysis is to determine whether the integration proposed is beneficial to the system in terms of thermodynamic performance, compared to the proposed systems in the open literature. The proposed system is simulated using Aspen Plus software, with two models for gasification. Some parametric studies are performed on the system to determine the effect of type of coal, steam flow rate in the single reheat supercritical Rankine cycle, and the main parameters of the membrane reactor on the overall energy and exergy efficiencies of the proposed system. The overall energy and exergy efficiencies of the proposed system are found to be 66.9% and 62.0% for Illinois #6 coal, and 60.7% and 57.0% for the Turkish coal Tuncbilek. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Coal gasification; Energy; Exergy; Carbon capturing; Hydrogen sulfide; UNDERGROUND COAL-GASIFICATION; PERFORMANCE; POWER; GAS; Chemistry; Electrochemistry; Energy & Fuels